Drosophila tracks carbon dioxide in flight. - Wasserman, S.; Salomon, A.; Frye, M.A. (Current Biology, 2013)
Carbon dioxide (CO(2)) elicits an attractive host-seeking response from mosquitos yet is innately aversive to Drosophila melanogaster despite being a plentiful byproduct of attractive fermenting food sources. Prior studies used walking flies exclusively, yet adults track distant food sources on the wing. Here we show that a fly tethered within a magnetic field allowing free rotation about the yaw axis actively seeks a narrow CO(2) plume during flight. Genetic disruption of the canonical CO(2)-sensing olfactory neurons does not alter in-flight attraction to CO(2); however, antennal ablation and genetic disruption of the Ir64a acid sensor do. Surprisingly, mutation of the obligate olfactory coreceptor (Orco) does not abolish CO(2) aversion during walking yet eliminates CO(2) tracking in flight. The biogenic amine octopamine regulates critical physiological processes during flight, and blocking synaptic output from octopamine neurons inverts the valence assigned to CO(2) and elicits an aversive response in flight. Combined, our results suggest that a novel Orco-mediated olfactory pathway that gains sensitivity to CO(2) in flight via changes in octopamine levels, along with Ir64a, quickly switches the valence of a key environmental stimulus in a behavioral-state-dependent manner.